Reverse transcriptase-polymerase chain reaction analysis of cytokeratin 19 expression in the peripheral blood mononuclear cells of normal female blood donors. - Novaes, M (1997)
BACKGROUND: Early detection of haematogenous dissemination of epithelial tumours afforded by the analysis of epithelial antigen expression in the peripheral blood mononuclear fraction (PBMN) and bone marrow may confer a worse prognosis to patients with carcinoma. Cytokeratin 19 is a protein normally expressed by epithelial cells including normal and malignant mammary cells. Previous studies have demonstrated that analysis of cytokeratin 19 expression by the reverse transcriptase-polymerase chain reaction (RT-PCR) can detect one epithelial cell in as many as 10(5)-10(7) haematopoetic cells. Despite its sensitivity concern has been voiced recently about the specificity of this technique owing to the detection of cytokeratin 19 expression in the PBMN of normal volunteers and the bone marrow of patients with haematological malignancies. AIMS: To assess the sensitivity and specificity of RT-PCR detection of cytokeratin 19 in PBMN of normal female blood donors. METHODS: Blood was taken from 52 normal female blood donors and PBMN separated through Fycol gradient centrifugation. Cytokeratin 19 was measured using a two step nested RT-PCR assay. RESULTS: No amplification was found in the first step for any of the samples studied, whereas in the second step amplification was observed in 10 of the 52 samples. Both steps could detect one MCF-7 cell (the cytokeratin 19 positive control) in 10(6) CEM (cytokeratin 19 negative control) cells. CONCLUSIONS: As both PCR steps are sensitive to the 10(-6) level, performing only the first amplification step may decrease the non-specificity of this method. Further studies are needed to define the specificity and sensitivity of this technique in blood and bone marrow specimens of women with breast cancer.